The Association Between Leukocyte Telomere Length and Cognitive Performance Among the American Elderly - Linghui, Deng; Shi, Qiu; Chi, Chen; Xiaolei, Liu; Lixing, Zhou; Zhiliang, Zuo; Birong, Dong (Frontiers in Aging Neuroscience, 2020)
Background: Age-related cognitive decline begins in middle age and persists with age. Leukocyte telomere length (LTL) decreases with age and is enhanced by inflammation and oxidative stress. However, whether shorter LTL correlates with cognitive decline remains controversial. Aims: We aimed to investigate the relation between LTL and cognitive decline in the American elderly. Methods: We used data from the 1999–2002 U.S. National Health and Nutrition Examination Survey (NHANES). We included participants aged 65–80 with available data on LTL and cognitive assessments. The cognitive function assessment used the digit symbol substitution test (DSST). We applied multivariate modelling to estimate the association between LTL and cognitive performance. Additionally, to ensure robust data analysis, we converted LTL into categorical variables through quartile and then calculated the P for trend. Results: After adjusting for age, CAD score, gender, race, BMI and educational level, LTL showed a positive correlation with DSST score (OR 3.47 [0.14, 6.79], P = 0.04). Additionally, to further quantify the LTL–DSST interaction, we found a similar trend when LTL was regarded as a categorical variable (quartile) (P for trend = 0.03). Conclusions: LTL was associated with cognitive capabilities among the elderly, implying that LTL might be a biomarker of cognitive aging.